2018
DOI: 10.1086/700275
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Youth Empowerment Programs on the Psychological Empowerment of Young People Aging Out of Foster Care

Abstract: This study examines the effects of youth empowerment programs (YEPs) on the psychological empowerment of young people aging out of foster care. Method: We used a two-group, cross-sectional survey to examine the effect of YEP participation on the psychological empowerment of youths aging out of Florida's foster care system. The study sample consisted of 193 young adults (99 YEP participants and 94 non-YEP participants), ages 18-24. Four dependent variables represented the 4 dimensions of psychological empowerme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…These same authors point out that empirical studies based on Zimmerman's conceptualization have focused on one or two components. Some have developed scales for measuring specific dimensions of empowerment, including: the Sociopolitical Control Scale (Zimmerman & Zahniser, 1991) (Maloney, 2015), the Youth Development and Empowerment Program Model (Batista et al, 2018;Bulanda & Johnson, 2016), the Transactional Partnering Model (Kim, et al 1998), Critical Youth Empowerment (Jennings, et al 2006) andEmpowerment Education Model (Mohajer &Earnest, 2009) based on Freire, among others. Such diversity poses a challenge for evaluation (Bulanda & Johnson, 2016).…”
Section: Research On Youth Empowerment Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These same authors point out that empirical studies based on Zimmerman's conceptualization have focused on one or two components. Some have developed scales for measuring specific dimensions of empowerment, including: the Sociopolitical Control Scale (Zimmerman & Zahniser, 1991) (Maloney, 2015), the Youth Development and Empowerment Program Model (Batista et al, 2018;Bulanda & Johnson, 2016), the Transactional Partnering Model (Kim, et al 1998), Critical Youth Empowerment (Jennings, et al 2006) andEmpowerment Education Model (Mohajer &Earnest, 2009) based on Freire, among others. Such diversity poses a challenge for evaluation (Bulanda & Johnson, 2016).…”
Section: Research On Youth Empowerment Indicatorsmentioning
confidence: 99%
“…Finally, tTo give one more example, the study conducted by Batista et al (2018) into the effects of a Youth Empowerment Program on young people in the foster care system evidenced an improvement in psychological empowerment. This study was based on the use of survey methods and a comparison group, and revealed how the young participants on the program increased their levels of perceived control, motivation to influence, sociopolitical skills, and participatory behavior.…”
Section: Research On Youth Empowerment Indicatorsmentioning
confidence: 99%
“…These might include school projects focused on important problems — such as school violence, student misconduct, property damage and vandalism, and parental involvement — or community projects targeting critical local issues — including food shortages for seniors, homelessness, child welfare, foster care, and adult literacy. Growing evidence indicates these programs not only increase students’ sense of control, self-efficacy, and pro-social behavior, but also positively affect their school performance (e.g., grades, effort, academic confidence, graduation rates; Batista, Johnson, & Friedmann, 2018; Zimmerman et al, 2018).…”
Section: Classroom Activities and Programsmentioning
confidence: 99%
“…Respecto a la problemática del egreso abrupto, para poder favorecer una transición gradual a la independencia, se recomienda que en la cotidianidad de las residencias se haga hincapié en el desarrollo de habilidades, la responsabilidad, autocuidado y cuidado mutuo a través del incentivo de intereses mediante talleres, clases o capacitaciones, otorgando información sobre sus oportunidades en ámbitos laborales y académicos. La preparación debe comenzar desde antes, contar con un acompañamiento emocional con personal capacitado y considerar un seguimiento luego de dejar la residencia (Day et al, 2012;Batista et al, 2018).…”
Section: Proyecciones De La Investigación Y Recomendacionesunclassified